Achievements and challenges in the delivery of bioactive molecules by nano-carbon-based systems. (16th August 2010) - Pastorin, Giorgia; Nayak, Tapas Ranjan; Ren, Yupeng
The strategic combination of bioactive molecules and drug delivery systems has the advantage of increasing the bioavailability of drugs while improving their safety profiles. Amidst the systems aimed to advance the pharmacological profile of otherwise unfavourable molecules, carbon-based nanomaterials (including nanoparticles, graphite, fullerenes, nanotubes and diamonds) have gained high popularity on the basis of: 1) reduced dimensions, which allow them to penetrate into narrow cellular compartments and accumulate in those areas where their presence is most required; 2) wide surface area, which could be functionalised with several groups or chains and simultaneously incorporate drugs, targeting molecules or fluorescent probes; 3) high resistance, due to their compact structure or the stiffness of the material. Despite these promising factors, this review highlights also some concerns on such carbon-nanosystems and which are mainly attributable to the inability of an exhaustive characterisation and to the potential risks associated with this still-unknown material.